Exploring sample size limits of AMS gas Ion Source 14C analysis at Cologneams. Issue 6 (December 2019) - Melchert, Jan Olaf; Stolz, Alexander; Dewald, Alfred; Gierga, Merle; Wischhöfer, Philipp; Rethemeyer, Janet
ABSTRACT: Increasing demands for small-scale radiocarbon ( 14 C) analyses required the installation of a "SO-110 B" type ion source (HVE Europa B.V.) at our 6 MV Tandetron AMS (HVE) dedicated for the direct injection of CO2 using either the gas injection system (GIS) from Ionplus AG or a EuroVector EA 3000 elemental analyzer (EA). We tested both systems with multiple series of 14 C-free and modern standards (2.5–50 µg C) combusted in quartz ampoules or EA containers and were able to quantify exogenous C introduced. In EA-GIS-AMS analysis exogenous C is mainly derived from the EA sample containers. Blank values for 50 µg C combusted in solvent-cleaned tin (Sn) vessels were 0.0127 ± 0.0012 F 14 C (boats) and 0.0090 ± 0.0010 F 14 C (capsules), while they were much higher for thermally cleaned silver (Ag) capsules. The processing of gas samples for GIS-AMS yields similar blank values corresponding to 0.30 ± 0.08 µg exogenous C with 0.93 ± 0.23 F 14 C consisting of 0.28 µg C modern and 0.02 µg C fossil C. The combustion of larger amounts of blank material (1 mg C) in a single quartz tube split into aliquots gives lower blanks (0.0064 ± 0.0008 F 14 C; 50 µg C). Thus, 14 C analysis of small, gaseous samples is now possible at CologneAMS.